Incarcerated Inguinal Hernia with Adhered Ileal Loop: A Case Report - Silwal, Mahesh (Nepal Medical College Journal, 2025)
About one-tenths of inguinal hernias become incarcerated, mainly secondary to benign causes. Incarcerated hernias are irreducible with intact blood supply to the contained part but might develop strangulation if not timely managed. Traditionally, open technique has been used to repair incarcerated or strangulated inguinal hernias, as it is probably the safest and the most expedient approach. A case of incarcerated inguinal hernia with adhered ileal loop, which is a rare finding, is reported in this article.